2009
DOI: 10.1007/s11192-009-1870-4
|View full text |Cite
|
Sign up to set email alerts
|

Countries positioning in open access journals system: An investigation of citation distribution patterns

Abstract: By their widespread availability and dissemination through open access media, scholarly outputs witness an improved visibility supposed to cause a better citation performance. However, due to the existence of the Matthew effect in science system, which affects users' perceptions of quality, ultimate effects of the enhanced visibility on different entities are obscure. Moreover, different attitudes towards open access give rise to a more strong quality dynamics in the open access world. Aiming to explore the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
1
5
0
1
Order By: Relevance
“…Of special note is the subject area label 'Multidisciplinary sciences'. While previous studies that investigated the OA citation advantage reported results on this 'subject area' (Dorta-González et al 2017;Sotudeh and Horri 2009), we argue that it should be excluded in analyses that specifically investigate subject areas. Our reasoning being that one disaggregates by subject area because citation behaviour differs among subject areas.…”
Section: Subject Areamentioning
confidence: 80%
See 1 more Smart Citation
“…Of special note is the subject area label 'Multidisciplinary sciences'. While previous studies that investigated the OA citation advantage reported results on this 'subject area' (Dorta-González et al 2017;Sotudeh and Horri 2009), we argue that it should be excluded in analyses that specifically investigate subject areas. Our reasoning being that one disaggregates by subject area because citation behaviour differs among subject areas.…”
Section: Subject Areamentioning
confidence: 80%
“…Lawrence 2001;Antelman 2004;Kurtz et al 2005;Hajjem et al 2005, Sotudeh andHorri 2007). These initial studies not only assisted with identifying the mechanisms through which an OA citation advantage could possibly be explained (Davis and Fromerth 2007;Sotudeh and Horri 2009), but also found that an OA citation advantage differs across the various types of OA (e.g. green, gold, hybrid) (Archambault et al 2014b, p. 20;Periances-Rodríguez andOlmeda-Gómez 2019, p. 1743) and subject areas (Dorta-González et al 2017).…”
Section: A Conceptual and Empirical Review Of The Open Access Citatiomentioning
confidence: 99%
“…The second stream of work examines whether existing metrics for evaluating journals accurately characterise OA journals with a twostage publication process (Bornmann et al, 2010). The third, and largest, stream of work examines the advantages of OA (Dong et al, 2006;Davis and Fromerth, 2007;Sotudeh and Horri, 2008;Sotudeh and Horri, 2009;Gentil-Beccot et al, 2010;Gaulé and Maystre, 2011;Koler-Povh et al, 2014;Wang et al, 2015) with the main focus on the scientific impacts of OA publishing. Papers deposited in open repositories receive higher numbers of citations (Davis and Fromerth, 2007;Gentil-Beccot et al, 2010;Koler-Povh et al, 2014), but there is no agreement on whether this effect is attributable to the open and early accessibility of deposited papers (Gentil-Beccot et al, 2010) or to their quality (Davis and Fromerth, 2007;Koler-Povh et al, 2014).…”
Section: Literature Review: What Is Known About the Transition To Oa mentioning
confidence: 99%
“…OJS 3 enables journal managers to migrate from offline to online management system. Starting from a manuscript / article posted by the author, the process of reviewing, tracking, and so forth until the manuscript is accepted for publication in a journal, everything can be done with OJS 3 [1]. According Willinsky (2005) with this system the process of sending manuscripts / articles (submission), assessment, editing, layout editing and publishing can be done online.…”
Section: Introductionmentioning
confidence: 99%